FEM analysis of temperature distribution and experimental study of microstructure evolution in friction interface of GH4169 superalloy. (5th November 2015) - Yang, Xiawei; Li, Wenya; Li, Jiang; Ma, Tiejun; Guo, Jia
Abstract: The linear friction welding (LFW) process is a very effective solid-state welding method. Friction process is very significant for temperature distributions on the surface between two contacting workpieces during LFW process. In this paper, a finite element method (FEM) model is implemented to analyze the temperature distributions in friction interface of GH4169 superalloy cylindrical specimens. The simulation studies were conducted using ABAQUS software. Temperature distributions during the simulation of one rotation of the pressure head on the specimen were simulated. Temperature distributions of specimens in the end of different rotations were also investigated. The validation experiments were conducted to validate the simulation results. The detailed microstructure investigations demonstrate that the temperature distributions obtained in the present model are correct. This friction model is able to simulate the friction process of the GH4169 superalloy, but further research about FEM models is still needed for more precise prediction of microstructure evolution in the friction process of this alloy. Graphical abstract: Highlights: Three dimensional FEM was used to calculate the temperature field. The surface morphology of grinding marks shows non-uniform distributions. A thin layer of fine grains was observed in the interface of grinding marks. Model is verified by experiments (width and morphology of grinding marks).